2018
DOI: 10.1051/matecconf/201820602004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Content Variation of the Different Recycled Wastes to the Properties of Concrete Paving Block

Abstract: Recycled concrete aggregates have been widely studied and used in concrete products nowadays. However, other recycled wastes, such as glass, have not been involved too much in recycled aggregate concrete studies. This paper aims to study the impact of the content variation of the different recycled wastes to the properties of the concrete paving block. In this paper, not only recycled coarse concrete aggregates, crushed glass are also used as the recycled aggregate in the concrete paving block in different rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In order to improve sustainable construction, investigations about the effects of the addition of non-biodegradable materials and wastes in the development of construction materials have been carried out. Some investigations have concluded that the addition of waste glass, like sand and crushed, can improve the strength of paving blocks and they met the technical specifications as a normal paving stone [3] y [4]. On the other hand, the authors [5] and [6], have concluded that the percentage of fired clay powder and palm kernel shell powder (pskp) affects the strength of the mortar and the concrete respectively so at the correct percentage they can be used as a new component for mortars and concrete.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve sustainable construction, investigations about the effects of the addition of non-biodegradable materials and wastes in the development of construction materials have been carried out. Some investigations have concluded that the addition of waste glass, like sand and crushed, can improve the strength of paving blocks and they met the technical specifications as a normal paving stone [3] y [4]. On the other hand, the authors [5] and [6], have concluded that the percentage of fired clay powder and palm kernel shell powder (pskp) affects the strength of the mortar and the concrete respectively so at the correct percentage they can be used as a new component for mortars and concrete.…”
Section: Introductionmentioning
confidence: 99%